039 Improved survival with abciximab if used during PCI for NSTEMI patients under 75 years of age. (22nd September 2015) - Wicks, E C; Rathod, K; Jones, D; Ludman, A; Jain, A; Rothman, M T; Knight, C; Mathur, A; Wragg, A
Abstract : Background: Use of GPIIb/IIIa inhibitors have been shown to improve both short and long-term outcome in patients undergoing early PCI post Non-ST elevation MI. Concerns over their side effect profile have lead to under-usage in current practise, especially in an ageing population. We investigated the effects of abciximab use during PCI for NSTEMI on all cause mortality comparing under and over 75 s. Methods: Clinical information was analysed from a prospective database on 3047 patients who underwent PCI following NSTEMI between October 2003 and December 2007 at a London centre. Information was entered at the time of procedure and outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS CCAD national audit. Results: There were 2492 patients under the age of 75 of which 51% (1268/2492) were treated with abciximab, this compared to 44% (244/555) of the over 75 s. In patients under 75 treated with abciximab there were higher rates of diabetes (24% vs 20%, p=0.02), previous MI (36% vs 26% p<0.0001) and previous PCI (20% vs 13%, p<0.0001). There were no differences in previous CABG or left main intervention between the two groups. In the over 75 s there were no significant differences. Patients under the age of 75 treated with abciximab had significantly improved outcomes compared to those who were not, both with decreased in hospital MACCE (1.3% vs 2.9%, p=0.01) and decreased long term mortality maintained over 5 years (p=0.0038) (Abstract 39 Figure 1). For the elderly population, a benefit was seen with decreased in-hospital MACE (1.0% vs 4.3% p=0.02), however no significant long term mortality benefit was seen. There was no significant increased bleeding noted in either the younger or older abciximab groups. Conclusions: Our data suggest a benefit of abciximab use during PCI for NSTEMI in patients under 75 years of age. Less benefit was seen in the older patient with no long-term mortality benefit.